2009
DOI: 10.1109/tasc.2009.2027609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress and Morphology on the Resistivity and Critical Temperature of Room-Temperature-Sputtered Mo Thin Films

Abstract: We report on the structural and electrical characterization of Mo thin films deposited at room temperature by RF magnetron sputtering. The effect of RF power on the morphology and residual stress of the films is analyzed. The films are under compressive stress and consist of densely packed columns with a lateral size on the order of 20 nm. The stress, critical temperature, and resistivity of the films are found to rise when increasing the ejected ion energy during the sputtering process. The changes in critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
3
20
1
Order By: Relevance
“…Over a wide range of deposition conditions, T c appears to be closely correlated with resistivity, which in turn is believed to be dominated by grain-boundary scattering. The observed correlation agrees with that typically observed for sputtered films 4,9 and can be understood by considering that disorder in the film smears the the electronic density of states, thus, for Mo leading to an enhancement of the density of states at the Fermi level 10,11 . Additionally, disorder could soften the phonon spectrum 12 .…”
Section: Ion-beam Assisted Deposition Of Mo Filmssupporting
confidence: 87%
See 1 more Smart Citation
“…Over a wide range of deposition conditions, T c appears to be closely correlated with resistivity, which in turn is believed to be dominated by grain-boundary scattering. The observed correlation agrees with that typically observed for sputtered films 4,9 and can be understood by considering that disorder in the film smears the the electronic density of states, thus, for Mo leading to an enhancement of the density of states at the Fermi level 10,11 . Additionally, disorder could soften the phonon spectrum 12 .…”
Section: Ion-beam Assisted Deposition Of Mo Filmssupporting
confidence: 87%
“…Two techniques are in common use for the deposition of high quality bilayers: a) e-beam evaporation onto heated substrates for Mo/Au 1 , and b) sputter deposition at room temperature for Mo/Cu 2,3,4,5 . While in principle the bilayer fabrication should be straightforward, in practice reproducibility remains a significant challenge, partly because the interactions of various process and materials parameters are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…We have found through careful control of film thickness uniformity and stress, that using this method we can achieve sufficiently repeatable results [5]. The effects of deposition conditions on Mo Tc have been studied in [6]. We have additionally found that the silicon surface condition can affect the Mo transition temperature by changing the as-deposited Mo film stress for identical deposition conditions.…”
Section: Fig 1 Fabrication Flowmentioning
confidence: 99%
“…Si 3 N 4 is cleaned with a KOH solution prior to deposition. This cleaning procedure and base pressure are crucial for the reproducibility and high quality of Mo, while bias voltage during sputtering controls the film stress, ultimately determining its T c and residual resistance ratio 11 . After Mo deposition, the pressure is changed to 6μbar and a 15nm-thick Au film is deposited in-situ by DC magnetron sputtering; typical deposition rates are respectively 0.2nm/s and 0.5nm/s for Mo and Au.…”
Section: Tes Fabricationmentioning
confidence: 99%
“…In previous work we demonstrated our ability to fabricate high quality, reproducible Mo thin films and Mo-based TES 10,11,12,13 . Now we have devised a development plan aimed at fabricating TES meeting X-IFU requirements.…”
Section: Introductionmentioning
confidence: 99%